Descriptions of two new species of click-beetle (Coleoptera: Elateridae) from Turkey Descriptions of two new species of click-beetle (Coleoptera: Elateridae) from Turkey - Platia, Giuseppe; Kabalak, Mahmut; Sert, Osman (Zootaxa, 2007)
In this study, two new species of click-beetles, Ampedus turcicus n. sp. and Athous (Orthathous) demirsoyi n.sp., are described from Turkey. The morphologies of these new species and their genital organs are described, photographs of each species and character details are provided, and distribution maps are given.